Exploratory and Confirmatory Factor Analysis of the Academic Motivation Scale (AMS)–Bahasa Indonesia - Natalya, Lina; Purwanto, Cynthia Vivian (Makara Human Behavior Studies in Asia, 2018)
Validity evidence based on internal structure is important for psychological measurements and this internal structure can be evaluated by factor analysis. Two types of factor analysis are often conducted on psychometric tests: confirmatory factor analysis (CFA) and exploratory factor analysis (EFA). This study compared the groupings of the 30-item Indonesian version of the Academic Motivation Scale(AMS–Bahasa Indonesia), using both CFA and EFA. The CFA of the data sample from 1,168 undergraduates indicated that all dimensions and sub dimensions of the AMS–Bahasa Indonesia had good internal structural validity. Each subdimension, dimension, and variable of the AMS–Bahasa Indonesia fulfilled the goodness of fit criteria (RMSEA ? 0.08; GFI ? 0.9; CR ? 0.7). The EFA showed that all items of the three dimensions grouped perfectly as designed by Vallerand et al. (1992), and the factor loading values of all items are greater than or equal to 0.4. Although there are cross loadings of items, it can be explained as why it occurs. The results of the internal consistency analysis showed that the AMS–Bahasa Indonesia is a reliable measurement (? ? 0.7). In conclusion the AMS–Bahasa Indonesia is a valid instrument for measuring academic motivation accurately and reliably.